RANCANG BANGUN ALAT PENGIRIS BAWANG MERAH (Allium Cepa, L) SEMI MEKANIS UNTUK MEMUDAHKAN PENANGANAN PASCA PANEN - Amrullah, Muhammad Syahrun; Wijaya, Mohammad; Jamaluddin, Jamaluddin (Jurnal Pendidikan Teknologi Pertanian, 2019)
This study aims to determine the design of onion slicer to facilitate farmers in handling post-harvest, and can also function as a tool that can be used by small businesses, especially fried onion business. The form of this research is the design of tools. The design of shallot slicer through several mechanisms including the manufacture of tool support, installation of material components such as hopper, pulley, v-belt, knife, and bearing. The research data was obtained from the results of testing tools by testing simple tools, design tools with 2 knives and also by designing using 4 knives, this tool uses an electric motor as a driving force to replace human power. Data analysis techniques are carried out quantitatively with statistics. The results of this study indicate that the design of tools with 2 and 4 knives has not run optimally.